An analysis on airline passenger satisfaction through services provided by international airline. (9th December 2022) - Moyeenudin, H.M.; Bindu, G.; Anandan, R.; Vijayakumar, M.
International airlines have been seeing a consistent change in menu based on their client's interest. This created an impact on the design of an advanced menu that is compiled for a complete diet to provide full nourishment based on airline. Food and beverage service quality has become a feature for international airline companies in contending with one another and in keeping their esteem and noticeable quality in the choice of their specific airline travellers, as the extending wants of aircraft passengers lead to a healthy eating regimen with a customised menu in regard to flight catering. International airlines of various destinations has expanded the variety of food and refreshment with quality according to passengers, further in customising the diet with their desires, and through quality of food and beverages, in order to retain their passengers especially to get them back later on airline. The objective of this study is to identify the quality of food and beverage provided to international airline travellers. Secondly, on knowing the various expectations of passengers like onboard facilities, by upgrading the menu as per passenger's expectation and by the nature of airline administrations, in order to satisfy them with the quality of service.